Cytobacts: Abundant and Diverse Vertically Seed-Transmitted Cultivation-Recalcitrant Intracellular Bacteria Ubiquitous to Vascular Plants - Thomas, Pious; Rajendran, Thekepat P.; Franco, Christopher M. M. (Frontiers in Microbiology, 2022)
We have recently described ‘Cytobacts’ as abundant intracellular endophytic bacteria inhabiting live plant cells based on the observations with callus and cell suspension cultures of grapevine and other plant species with the origin ascribable to field explants. In this study, we investigated the prevalence of such cytoplasmic bacterial associations in field plants across different taxa, their cultivability, the extent of taxonomic diversity, and explored the possibility of their embryo-mediated vertical transmission. Over 100 genera of field plants were surveyed for ‘Cytobacts’ through bright-field live-cell imaging as per our previous experience using fresh tissue sections from surface-sterilized shoot-tissues with parallel cultivation-based assessments. This revealed widespread cellular bacterial associations visualized as copious motile micro-particles in the cytoplasm with no or sparse colony forming units (CFU) from the tissue-homogenates indicating their general non-cultivability. Based on the ease of detection and the abundance of ‘Cytobacts’ in fresh tissue sections, the surveyed plants were empirically classified into three groups: (i), motile bacteria detected instantly in most cells; (ii), motility not so widely observed, but seen in some cells; and (iii), only occasional motile units observed, but abundant non-motile bacterial cells present. Microscopy versus 16S-rRNA V3-V4 amplicon profiling on shoot-tip tissues of four representative plants -tomato, watermelon, periwinkle, and maize- showed high bacterial abundance and taxonomic diversity (11-15 phyla) with the dominance of Proteobacteria followed by Firmicutes/ Actinobacteria, and several other phyla in minor shares. The low CFU/ absence of bacterial CFU from the tissue homogenates on standard bacteriological media endorsed their cultivation-recalcitrance. Intracellular bacterial colonization implied that the associated organisms be able to transmit vertically to the next generation through the seed-embryos. Microscopy and 16S-rRNA V3-V4 amplicon/ metagenome profiling of mature embryos excised from fresh watermelon seeds revealed heavy embryo colonization by diverse bacteria with sparse or no CFU. Observations with grapevine fresh fruit-derived seeds and seed-embryos endorsed the vertical transmission by diverse cultivation-recalcitrant endophytic bacteria (CREB). By and large, Proteobacteria formed the major phylum in fresh seed-embryos with varying shares of diverse phyla. Thus, we document ‘Cytobacts’ comprising diverse and vertically transmissible CREBs as a ubiquitous phenomenon in vascular plants.